Effects of Butorphanol With Alfaxalone or Dexmedetomidine on Feline Splenic Size and Appearance on Ultrasound and Computed Tomography - Finck, Cyrielle; Steagall, Paulo; Beauchamp, Guy (Frontiers in Veterinary Science, 2021)
The purpose of the study was to determine the effects of intramuscular butorphanol with dexmedetomidine or alfaxalone on feline splenic size, echogenicity, and attenuation using ultrasound and computed tomography (CT). Ten healthy research cats underwent ultrasound and CT without sedation (controls), 15 minutes after protocol AB (alfaxalone 2 mg/kg and butorphanol 0.2 mg/kg) and 10 minutes after protocol DB (dexmedetomidine 7 μg/kg and butorphanol 0.2 mg/kg), with a one-week wash-out period between each sedation, using a cross-over study design. Images were randomized and anonymized for evaluation by a board-certified radiologist. On ultrasound, the sedative protocols affected splenic thickness, at the body and the tail (p = 0.002 and p = 0.0003, respectively). Post-hoc tests revealed that mean ± SEM thickness was greater after AB (body: 10.24 ± 0.30 mm; tail: 7.96 ± 0.33 mm) than for the control group (body: 8.71 ± 0.30 mm; tail: 6.78 ± 0.33 mm), while no significant difference was observed following DB. Splenic echogenicity was unchanged between treatments (p = 0.55). On CT, mean ± SEM splenic volume was increased after AB (37.82 ± 1.91 mL) compared to the control group (20.06 ± 1.91 mL) (p < 0.0001), but not after DB (24.04 ± 1.91 mL). Mean splenic attenuation increased after AB (p=0.0009), but not DB. Protocol DB may be preferable for profound sedation in cats while avoiding changes in feline splenic imaging. When protocol AB is selected, splenomegaly should be expected, though mild on ultrasound. The increased splenic attenuation after AB is unlikely to be clinically relevant.